Editorial: Resilience surprises! - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2024)
In contrast with the doom and gloom of many of the contributions published in a recent issue of New Agenda which marked 30 years of democracy in South Africa, this issue of New Agenda brings a close to the journal for 2024 with a series of articles that reflect and record the fortitude of our democracy, and the people’s determination to defend and preserve it. The Institute for African Alternatives (IFAA) has made the unusual editorial decision of publishing in this issue a comprehensive three-part focus on a subject that has preoccupied us greatly over the past years – the relationship between corruption and democracy.